Epigenetically reprogrammed methylation landscape drives the DNA self-assembly and serves as a universal cancer biomarker. Issue 1 (December 2018) - Sina, Abu; Carrascosa, Laura; Liang, Ziyu; Grewal, Yadveer; Wardiana, Andri; Shiddiky, Muhammad; Gardiner, Robert A.; Samaratunga, Hemamali; Gandhi, Maher K.; Scott, Rodney J.; Korbie, Darren; Trau, Matt
Abstract Epigenetic reprogramming in cancer genomes creates a distinct methylation landscape encompassing clustered methylation at regulatory regions separated by large intergenic tracks of hypomethylated regions. This methylation landscape that we referred to as Methylscape is displayed by most cancer types, thus may serve as a universal cancer biomarker. To-date most research has focused on the biological consequences of DNA Methylscape changes whereas its impact on DNA physicochemical properties remains unexplored. Herein, we examine the effect of levels and genomic distribution of methylcytosines on the physicochemical properties of DNA to detect the Methylscape biomarker. We find that DNA polymeric behaviour is strongly affected by differential patterning of methylcytosine, leading to fundamental differences in DNA solvation and DNA-gold affinity between cancerous and normal genomes. We exploit these Methylscape differences to develop simple, highly sensitive and selective electrochemical or colorimetric one-step assays for the detection of cancer. These assays are quick, i.e., analysis time ≤10 minutes, and require minimal sample preparation and small DNA input. DNA methylation is an epigenetic modification that control genetic programs. Here, the authors found that the methylation landscape influences the physicochemical properties of DNA and that it can serve as a universal cancer biomarker, and developed a one-step assay for the detection of cancer DNA.